STUDY OF THE EFFECT OF COMPOUND EXERCISE ON DEPRESSION, PSYCHOLOGICAL PROBLEM OF WOMEN'S MENOPAUSAL PERIOD: महिलाओं की रजोनिवृत्ति काल की मनोवैज्ञानिक समस्या अवसाद पर यौगिक अभ्यास के प्रभाव का अध्ययन - Rauniyar, Ranjana (International Journal of Research -GRANTHAALAYAH, 2017)
The aim of present investigation is to study the effect of Special Yoga Package (Sukshm Vyayam, Anulom Vilom, Bhramari, Om Chanting & Yog Nidra) on those women who are suffering from ‘Depression’ during menopause. The sample consist 60 women from Badarpur, New Delhi for Yogic practices. ‘t’ test computed for the pre & post Yogic practices. Result indicates that the women, who did Yoga practices, lower the effect of depression